Improving Senior High School Students’ Ability in Speaking Using “Everyone is A Teacher Here Strategy” - Tarigan, Surya Setiadi; Fahmi, Hasrul; Utami, Sury (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
This research was Classroom Action Research, aimed to improve the students’ ability in speaking by using everyone is a teacher here strategy. The sample of this study was XI-IPA, which consisted of 14 students of SMA Free Methodist Medan. This research was done in two cycles. Each cycle was consisted of four steps, namely, planning, action, observing, and reflecting. The data of this study were obtained by using a test, interview sheet and observation sheet. Based on the analysis, it was found that there was an improvement on the students’ ability in speaking from each cycle. It was showed from the mean of pre-test, which was 57,5. In the first cycle, there was an improvement of the result of the students’ mean, which was 68,4 and for the second cycle there was an increasing of the students’ mean which was 79,1. Moreover, in pre-test session there was 21% (3 students) who got point of ≥ 70. In post-test for cycle I, there was 50% (7 students) who got point of ≥ 70. In post-test for cycle II, there was 78% (11 students) who got point of ≥ 70. So, the total percentage of the students’ increasing from the pre-test to the post-test cycle II was 49%. And it indicates that the using everyone is a teacher here strategy can improve the students’ ability in speaking.